Seroprevalence of herpes simplex virus type-2 among patients attending the Sexually Transmitted Infections Clinic in Jos, Nigeria - Yusuf A. Agabi; Edmund B. Banwat; John D Mawak; Patricia M Lar; Nanma Dashe; Michael M Dashen; Moses P Adoga; Felicia Y Agabi; Hashimu Zakari (Journal of Infection in Developing Countries)
Background: Infection with Herpes Simplex Virus Type-2 (HSV-2) is the primary cause of genital herpes and the most common cause of genital ulcer disease (GUD) worldwide.  There is little information on the prevalence of HSV-2 in Nigeria.